PESTISIDA NABATI PEMBASMI HAMA RAMAH LINGKUNGAN UNTUK PETANI TEBUWUNG (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2019)
This paper aims to determine the potential of flora of the Village of Tebuwung which can be used as vegetable or organic pesticides. The author along with the appropriate technology division which numbered thirteen people conducted three surveys and observations in Tebuwung Village in the context of implementing a community service program. The results of the survey can be used as data and materials to mapping problems and find useful solutions for Tebuwung Village. The method used in this writing is descriptive qualitative. While the method of implementing activities is the provision of material and practice with the subject. The results obtained from this activity were that the subjects had never carried out simulations or practices using basic materials which were used as vegetable or organic pesticides. The ingredients used are: galangal, lemongrass leaves, neem leaves and tobacco which are three years old. Subjects have also never marketed galangal, lemongrass leaves, neem leaves, and three-year-old tobacco into products that are of high selling value. It is expected that in the subsequent service activities, a sustainable agenda can be implemented using the same products with a wider marketing scope.